INVESTIGATION OF THE FACTORS PREDISPOSING DRUG ABUSE BY YOUTHS IN KANO METROPOLIS, NIGERIA - Ahmad, Bala; Saleh, Bala Dawakin Tofa (African Journal of Social and Behavioural Sciences, 2024)
The abuse of drugs and other dangerous substances constitutes one of the major social problems bedevilling youth today. This undesirable and anti-social act hinders their progress and predisposes them to arbitrary over-dependence or misuse of drugs, thereby jeopardizing society’s future, and destroying societal moral values. This study aimed to investigate the factors associated with drug abuse among young people in Kano metropolis and to investigate how joblessness predisposes young people to substance abuse in Kano Metropolis. Additionally, we examined the influence of peer groups on the spread of drug abuse among the young people in Kano Metropolis, studied the influence of broken homes and parenting styles as factors in drug abuse in Kano Metropolis and investigated whether corruption among law enforcement agents led to drug abuse among young people in Kano Metropolis. This study reviewed related literature on drug abuse by youth, including; the concept of drug abuse, the types of drugs commonly abused and effects of the abuse. The theoretical framework of the study included two relevant theories; differential association theory, and availability proneness theory of which differential association theory was adopted as the leading theoretical guide for the research. The methodology used was descriptive survey research; the sample size for the study was 350 respondents selected through availability, purposive and snowballing sampling techniques and 322 questionnaires were returned on the basis of which the analysis was performed. A questionnaire and in-depth interview were used for data collection, and both the qualitative and quantitative data obtained were analysed using relevant statistical methods. The findings revealed that peer group influence, unemployment and poor parenting style have a significant influence on precipitating drug abuse among youth, while corruption within law enforcement agencies reinforced factors that help the spread and persistence of drug abuse among youth in Kano Metropolis. Therefore, based on the study findings, it was recommended that the government should build more institutions of higher learning and subsidize education to enable teeming youth to acquire knowledge for better living. Parents and guardians should be extra vigilant in monitoring their children’s movements and behaviour as well as with whom they associate. Finally, NGOs, CBOs, and religious and community leaders should embark on sensitization campaigns and preaching on the dangers of drug abuse.